The stratigraphic significance of early Cambrian (Series 2, Stage 4) trilobites from the Smith Bay Shale near Freestone Creek, Kangaroo Island. Issue 2 (17th February 2021) - Jago, J. B.; Bentley, C. J.; Paterson, J. R.; Holmes, J. D.; Lin, T. R.; Sun, X. W.
Abstract: The fossiliferous lower Cambrian (Series 2) successions along the north coast of Kangaroo Island, South Australia—known collectively as the Kangaroo Island Group—can be divided into two main areas: a western succession located between Snelling Beach and Smith Bay, which comprises the Mt McDonnell Formation (base), Stokes Bay Sandstone and Smith Bay Shale; and an eastern succession that extends from Emu Bay to Point Marsden, represented by exposures of the White Point Conglomerate (base), Marsden Sandstone, Emu Bay Shale and Boxing Bay Formation (top), with an overlap in the Cape d'Estaing/Emu Bay area. Some previous interpretations of the Kangaroo Island Group stratigraphy suggest that the western succession stratigraphically underlies the eastern succession. Most of the previously reported and described Cambrian fossils come from the eastern succession, especially the internationally significant Emu Bay Shale Konservat-Lagerstätte . Here we report the trilobites Redlichia takooensis and Balcoracania dailyi from the Smith Bay Shale near Freestone Creek, indicating that the eastern and western successions are at least partly contemporaneous. The present investigation indicates that the Smith Bay Shale of the western succession can be correlated with the stratigraphic interval represented by the Marsden Sandstone and the overlying Emu Bay Shale of the eastern succession. The Kangaroo Island Group was deposited as part of a fan delta system with the eastern succession representing the proximal part, and the western succession representing the distal part of the fan delta. The lack of substantial conglomerate units within the Kangaroo Island Group to the west of Cape d'Estaing suggests that the tectonic uplift that led to the deposition of the White Point Conglomerate was concentrated in the area immediately to the north of Emu Bay.